CATATAN KEKAYAAN JENIS GASTROPODA DI PESISIR PULAU LETI, KAWASAN BANDA SELATAN - Muhammad Masrur Islami (BERITA BIOLOGI, 2017)
Note on species richness of gastropods in coastal area of Leti Island, southern Banda was conducted as a part of Southern Banda Expedition on October 7-16, 2015. Sample collection was carried out by hand picking in Serwaru, Tutukey village, Leti Island, Southwest Maluku.  A total of 125 individu from 25 species of gastropods was found. The highest number of individu is Clypeomorus moniliferus. Generally, gastropods found in this area were associated with rocky hard substrate.